An Actor-Critic Algorithm with Function Approximation for Risk Sensitive Cost Markov Decision Processes - Guin, Soumyajit; Borkar, Vivek S.; Bhatnagar, Shalabh (IEEE transactions on automatic control, 2025)
In this paper, we consider the risk-sensitive cost criterion with exponentiated costs for Markov decision processes and develop a model-free policy gradient algorithm in this setting. Unlike additive cost criteria such as average or discounted cost, the risk-sensitive cost criterion is less studied due to the complexity resulting from the multiplicative structure of the resulting Bellman equation. We develop an actor-critic algorithm with function approximation in this setting and provide its asymptotic convergence analysis. We also show the results of numerical experiments that demonstrate the superiority in performance of our algorithm over other recent algorithms in the literature.